Ophthalmic manifestations of atopic dermatitis - Pietruszyńska, Marta; Zawadzka-Krajewska, Anna; Duda, Patrycja; Rogowska, Monika; Grabska-Liberek, Iwona; Kulus, Marek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Atopic dermatitis is a chronic condition of complex etiology, whose clinical course involves remission and recurrence. It is not an isolated disease entity affecting only the skin, but one that co-occurs with disorders of other organs. Numerous literature reports have long confirmed the relationship between the disorder and a growing number of ophthalmic manifestations such as keratoconus and retinal detachment. Further studies are required to establish the cause of correlations and to allow for implementation of appropriate prophylaxis and treatment. The aim of the present paper is to review published literature regarding the correlation between atopic dermatitis and ophthalmic manifestations in adults and children.